16th International Conference and Exhibition on Electricity Distribution (CIRED 2001) 2001
DOI: 10.1049/cp:20010890
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network-based distribution substation and feeder load forecast

Abstract: Artificial Neural Networks (ANNs) have been successfully applied to the problem of forecasting future load values, especially in the short term framework (a few minutes to a few hours ahead). Traditional analytical models have shown difficulties when dealing with (i) the highly variable demand curve shapes, (ii) some independent variables that exhibit random behaviour, and (iii) the identification of variables that could explain relevant load variations, such as weather variables. Current available ANN applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…This procedure aims at supplying more accurate conditions of the loading behaviour, every 15 minutes, for five future intervals -¼ hour, ½ hour, 1 hour, 2 hours and 4 hours ahead. This module has been extensively studied [1]. Figure 2 shows one of such forecast.…”
Section: C I I R R E E D Dmentioning
confidence: 99%
“…This procedure aims at supplying more accurate conditions of the loading behaviour, every 15 minutes, for five future intervals -¼ hour, ½ hour, 1 hour, 2 hours and 4 hours ahead. This module has been extensively studied [1]. Figure 2 shows one of such forecast.…”
Section: C I I R R E E D Dmentioning
confidence: 99%
“…In this reference it is shown that data shifts, due to feeders switching, contaminates registers and reduces forecasting accuracy in the medium and long term. In addition, feeders' reconfiguration has been recognised as an important element for estimating future demand values in the shortterm (24 h ahead) [15]. In that reference the authors conclude that switching operation in primary networks has a substantial impact on load profiles, hence, producing errors in future demand forecasting.…”
Section: Introductionmentioning
confidence: 99%
“…In [2], a branch-and-bound model is proposed for the selection of the substation location. In general, different mathematical programming formulations and techniques have been proposed and applied to the location problem of electrical distribution substations: simulating annealing [4,5], genetic algorithms [6,7], evolution strategies [8,9], particle swarm optimization [10], bacterial colony chemotaxis [11,12], evolutionary programming [13] and neural network [14]. In general, different mathematical programming formulations and techniques have been proposed and applied to the location problem of electrical distribution substations: simulating annealing [4,5], genetic algorithms [6,7], evolution strategies [8,9], particle swarm optimization [10], bacterial colony chemotaxis [11,12], evolutionary programming [13] and neural network [14].…”
Section: Introductionmentioning
confidence: 99%